Executive Functions During Submaximal Exercises in Male Athletes: Role of Blood Lactate - Coco, Marinella; Buscemi, Andrea; Cavallari, Paolo; Massimino, Simona; Rinella, Sergio; Tortorici, Marta Maria; Maci, Tiziana; Perciavalle, Vincenzo; Tusak, Matej; Di Corrado, Donatella; Perciavalle, Valentina; Zappalà, Agata (Frontiers in Psychology, 2020)
The present study was carried out to determine, in 20 healthy young male athletes, whether an aerobic exercise, performed at two different intensities, is able to affect executive functions. For this purpose, we used the Stroop Colour Word Test (SCWT), for evaluating the ability to inhibit cognitive interference, and Trail Making Test (TMT), for assessing organized visual search, set shifting, and cognitive flexibility. Simple Reaction Time (RT), measure of perception and response execution, was also evaluated. The experimental protocol included the measure of blood lactate levels with the aim of assessing possible relations between lactate blood values and the selected executive functions after a 30 min steady-state test performed at 60% and at 80% of VO2max. The results showed that a 30-minute aerobic exercise is not associated with a worsening of executive functions unless it is performed at such an intensity that blood lactate levels are increased above 4 mmol/l.